Optimal serving strategy for vehicle-to-grid business: service agreement, energy reserve estimation, and profit maximization - Peng, Chen; Niu, Yajie (Frontiers in Energy Research, 2023)
To advocate the adoption of electric vehicle (EV) technologies, this paper studies a practical operating paradigm for running a charge park V2G service business. The operating paradigm consists of a service agreement and two consecutive day-ahead analyses. Specifically, i) the service agreement underpins the communication pattern between EV owners and the V2G service operator, ii) day-ahead analysis-I estimates the V2G energy reserve distribution, and iii) day-ahead analysis-II aims to maximize profit by optimizing decision variables for the scheduled day, such as the output period and sale price of the V2G energy. Correspondingly, the contributions of this paper are three-fold. First, the major principles behind the design of a service agreement are highlighted, and a practical service agreement that abides the principle is formed. Second, for day-ahead analysis-I, this paper proposes a V2G energy reserve modeling method for rapid estimation of V2G energy reserve distribution, which is applied to a case study of New York City working and recreational environment charge parks. Third, for day-ahead analysis-II, an evaluation framework is proposed, which provides various metrics for characterizing the V2G output capacity. The metrics evaluation and profit maximization methods are presented with theoretical results, and are verified also by computer experiments. For example, we show that for the simulated environment with peak time-of-use hours [13:00,16:00] and V2G output period [13:00,14:00], the V2G output power threshold 61kW selected by our method achieves almost maximum scheduled day profit (true maximum achieved at 60kW).